Advanced manufacturing technology and cutting tools : selected, peer reviewed papers from the 2011 Seminar on Advanced Manufacturing Technology and Cutting Tools, August 20-22, 2011, Shanghai, China - Wang, Yongguo (Advanced materials research ;, 2012)
China is the world's largest market for machine- and cutting-tools, so advanced manufacturing technology and cutting tools can be expected to enjoy not only a good market share but also huge opportunities for development and advancement. The present volume contains 28 peer-reviewed papers selected from among the 60 (from academia and industry) presented at the seminar on Advanced Manufacturing Technology and Cutting Tools (SAMTCT2011) which was held during the 20-22th August 2011 in Shanghai (China). This work presents readers with a broad overview of recent advances in the fields of manufacturing technology and cutting tools. China is currently the biggest market for manufacturing technology and cutting tools in the world. It is natural, therefore, that this seminar has been held at Shanghai University since 2009. This collection of 28 peer-reviewed papers covers subjects ranging from vibration tapping to nano-indentation, as applied to a variety of materials.